(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The objective of the present study is to Estimate risk factors and microbiological profile of blood samples of septicaemic patients. In the current study combined disc diffusion test (CDDT) recommended by CLSI was considered as the standard method. The validity of all other tests was compared with the standard tests.